2022
DOI: 10.1186/s12870-022-03696-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of GARP superfamily genes in response to nitrogen and phosphorus stress in Spirodela polyrhiza

Abstract: Background GARP transcription factors perform critical roles in plant development and response to environmental stimulus, especially in the phosphorus (P) and nitrogen (N) sensing and uptake. Spirodela polyrhiza (giant duckweed) is widely used for phytoremediation and biomass production due to its rapid growth and efficient N and P removal capacities. However, there has not yet been a comprehensive analysis of the GRAP gene family in S. polyrhiza. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…The members of the NIGT1 (Nitrate-Inducible GARP-Type Transcriptional Repressor-1) subfamily in the superfamily of GARP transcription factors [ 59 ], participate in fine-tuning of gene expression in response to the plant nitrogen and phosphorus status [ 60 ]. The proteins bind to two types of cis -elements, GAATC and GAATATTC demonstrating dual modes of promoter recognition [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The members of the NIGT1 (Nitrate-Inducible GARP-Type Transcriptional Repressor-1) subfamily in the superfamily of GARP transcription factors [ 59 ], participate in fine-tuning of gene expression in response to the plant nitrogen and phosphorus status [ 60 ]. The proteins bind to two types of cis -elements, GAATC and GAATATTC demonstrating dual modes of promoter recognition [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a total of 146 BnaGARPs were identified (Table S1). A previous study has revealed 56 GARPs in A. thaliana, 69 GARPs in Camellia sinensis, and 35 GARPs in S. polyrhiza [8,10,50], suggesting that the GARP TF family is ubiquitous in plants (Table S11). The GARP gene family in rapeseed is larger than those in other plant species, which might be due to complex whole genome duplication and subsequent evolution of the rapeseed genome.…”
Section: An Integrated Bioinformatics Analysis Provided Comprehensive...mentioning
confidence: 89%
“…GARP transcription factors assume crucial functions in plant growth and their reaction to environmental stimuli. For instance, GARP's NIGT1 genes respond to phosphorus (P) and nitrogen (N) stresses, with some being downregulated following nitrogen stresses (NS) treatment [ 62 ]. Additionally, B3 subfamily proteins within the ERF family are associated to the regulation of secondary metabolites [ 63 ].…”
Section: Discussionmentioning
confidence: 99%